49 The biology of paediatric central nervous system tumours at post-mortem. (22nd November 2019) - Smolicz, Izabella; Fairchild, Amy; Pickles, Jessica; Stone, Thomas; Chalker, Jane; Zapata, Jamie Gonzalez; Wilkhu, Lisa; Yasin, Shireena; Merve, Ashirwad; Harding, Brian; Hargrave, Darren; Sebire, Neil; et al.
Abstract : Background: Central nervous system (CNS) tumours are the leading cause of childhood cancer deaths. There is little understanding of why tumours become untreatable but it is likely their biology changes over time and across space as they spread. One way to understand such advanced disease is to study the tumour biology at autopsy. We assembled a cohort of cases who had undergone autopsy for a childhood tumour. We assessed factors that could affect tumour biology in advanced disease and the feasibility of using archival post-mortem tissue with modern genomic technologies. Methods: Cases were identified through BRAIN UK and local databases. Clinico-pathological data was analysed for local cases. Twenty-seven cases underwent DNA methylation array profiling and data was processed in R using the DKFZ CNS tumour classifier and Conumee package. Results: We identified over 200 post-mortem paediatric CNS tumours across the UK. Among local cases (n=89), the median age was 3.8 years (range 0-31) and the median time between presentation and death was 4.5 months (range 0-144). At time of death, 46% of patients had not received cancer treatment compared to 54% who were receiving or had received treatment; 24% of patients were receiving palliative care. The cohort included a wide range of tumour types and origins. We had anticipated widespread dissemination in most cases but only in 68% of cases did the tumour infiltrate an area outside its origin. We could derive a confident diagnosis in 38% of cases using methylation data and in these, the molecular diagnosis matched the histology. Copy number changes could be interpreted in 81% of cases. Conclusions: We established a diverse post-mortem paediatric CNS tumour cohort and demonstrated that both previously known and novel genomic aberrations could be identified within this tissue. Future work will investigate how advanced tumour biology changes in time and space.